Effects of a therapeutic suit based on myofascial meridians on postural control and balance in children with cerebral palsy: a multiple-baseline, single-subject study - Cruz, Thalita Karla Flores; Souto, Deisiane Oliveira; Capuchinho, Rafhael Guimarães; Lima, Arthur Felipe Barroso de; Nascimento, Amanda Aparecida Alves Cunha; Silva, Ianara Pereira; Santana, Patrícia Aparecida Neves; Criscoullo, Lia Constantino; Haase, Vitor Geraldi (Frontiers in Pediatrics, 2025)
AimTo investigate the effects of an intervention programme based on the TREINI Exoflex therapeutic suit on balance, postural control, activity, and participation outcomes in children with cerebral palsy (CP).MethodA multiple-baseline, single-subject A/B research design was used. Balance, postural control, mobility, activities of daily living (ADLs), and goal attainment measures were collected for four children with CP. The intervention was a programme designed for the use of a therapeutic suit, that is, the TREINI Exoflex. The 2-SD band and percentage of non-overlapping data methods were used to compare outcomes between the baseline and intervention phases.ResultsThe intervention improved balance and postural control in all four children. The scope of the intervention on activity and participation outcomes varied between children. All children showed improvements in at least one stipulated goal and two in mobility and ADLs. Improvements in goal achievement occurred mainly for balance-related goals, whereas behavioural goals were not achieved.ConclusionThe results of this study support the use of the TREINI Exoflex suit during functional activities by children with CP. Future research should examine the effects of this approach in children of different ages and at different functional levels.